2022
DOI: 10.3390/plants11050620
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Calcium Forms in Lichens from Travertine Sites

Abstract: Lichens are symbiotic organisms with an extraordinary capability to colonise areas of extreme climate and heavily contaminated sites, such as metal-rich habitats. Lichens have developed several mechanisms to overcome the toxicity of metals, including the ability to bind metal cations to extracellular sites of symbiotic partners and to subsequently form oxalates. Calcium is an essential alkaline earth element that is important in various cell processes. Calcium can serve as a metal ligand but can be toxic at el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 37 publications
0
1
0
Order By: Relevance
“…Taking into account that Calvatia candida and Battarrea phalloides Table 2 data indicate that Ca content in Artemisia lerchiana, Calvatia candida and Battarrea phalloides are 11.8 and 31.9 times lower, respectively, than Ca level in lichen. Lichen Ca coating in the form of Ca oxalate crystals in dry habitats can be facilitated by the abundance of Ca in the substrate [16] and is supposed to contribute to water conservation in thalli [17,18]. In this respect, Ca hyperaccumulation in D. ocellatus may be considered as a specific form of protection against active oxygen forms and UV radiation excess [19][20][21].…”
Section: Mineral Compositionmentioning
confidence: 99%
“…Taking into account that Calvatia candida and Battarrea phalloides Table 2 data indicate that Ca content in Artemisia lerchiana, Calvatia candida and Battarrea phalloides are 11.8 and 31.9 times lower, respectively, than Ca level in lichen. Lichen Ca coating in the form of Ca oxalate crystals in dry habitats can be facilitated by the abundance of Ca in the substrate [16] and is supposed to contribute to water conservation in thalli [17,18]. In this respect, Ca hyperaccumulation in D. ocellatus may be considered as a specific form of protection against active oxygen forms and UV radiation excess [19][20][21].…”
Section: Mineral Compositionmentioning
confidence: 99%
“…Lichens are symbiotic organisms with an extraordinary capability to colonize areas of extreme climate and heavily contaminated sites, such as metal-rich habitats. Lichens have developed several mechanisms to overcome the toxicity of metals, including the ability to bind metal cations to extracellular sites of symbiotic partners and to subsequently form oxalates [8].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that lichens are desiccation-tolerant organisms that can survive in harsh environments where higher plants cannot survive [7,8]. Lichens are often found in a variety of extremely dry habitats such as rock surfaces, the Antarctic cold desert and hot deserts [9,10]. In these habitats, the water supply is not delivered by rain but rather in the form of fog, dew or humidity [8,11].…”
Section: Introductionmentioning
confidence: 99%